Multiple sclerosis prevalence in Ireland: relationship to vitamin D status and HLA genotype. Issue 3 (19th January 2011) - Lonergan, R; Kinsella, K; Fitzpatrick, P; Brady, J; Murray, B; Dunne, C; Hagan, R; Duggan, M; Jordan, S; McKenna, M; Hutchinson, M; Tubridy, N
Abstract : Background: The relationship between prevalence of multiple sclerosis (MS) and latitude may be due to both genetic and environmental factors. The hypothesis that, in Ireland, MS prevalence is increasing and that north–south differences relate to variation in serum 25-hydroxyvitamin D (25(OH)D) levels was tested in this study. Patients and methods: Patients and matched control subjects were identified in counties Donegal, Wexford and South Dublin through multiple sources. Prevalence was determined. Blood samples were taken for serum 25(OH)D and serum intact parathyroid hormone measurement, and DNA was extracted. Results: Prevalence in 2007 was significantly greater in Donegal (northwest) (290.3/105, 95% CI 262.3 to 321.7) compared with 2001 (184.6/105; 162 to 209.5). In Wexford (southeast), there was a non-significant increase in prevalence in 2007 compared with 2001. Prevalence was significantly higher in Donegal than in Wexford (144.8/105; 126.7 to 167.8, p<0.0001) and South Dublin (127.8/105; 111.3 to 148.2, p<0.0001). Overall, mean 25(OH)D levels were low and did not differ between patients (38.6 nmol/l) and controls (36.4 nmol/l) However, significantly more patients than controls had 25(OH)D levels <25 nmol/l (deficiency) (p=0.004). Levels of 25(OH)D (mean 50.74 nmol/l) were significantly higher in South Dublin (area with lowest prevalence) (p<0.0001) than in Donegal or Wexford. HLA DRB1*15 occurred most frequently in Donegal (greatest MS prevalence) and least frequently in South Dublin. Conclusion: Vitamin D deficiency is common in Ireland. Latitudinal variation in MS probably relates to an interaction between genetic factors and environment (25(OH)D levels), and MS risk may be modified by vitamin D in genetically susceptible individuals.